1981
DOI: 10.1051/rnd:19810404
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of hepatic enzyme activities to methionine excess

Abstract: Summary. Two groups of adult male rats 8 weeks old were fed a 10 p. 100 protein (casein) diet with or without 2 p. 100 methionine. After 8 rats in each group were killed at 10 a.m. on experimental days 1, 2, 4, 8 and 21, we studied the profiles of plasma non-esterified fatty acids (NEFA) and of the hepatic activities of pyruvate kinase (PK), phosphoenolpyruvate carboxykinase (PEPCK), glucose-6-phosphate dehydrogenase (G6PDH), malic enzyme (ME), acetyl-CoA-carboxylase (Ac.CoA carbox), alanine aminotransferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

1982
1982
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Harper, Becker and Stucki (16) suggested that the more protein an animal (rat) eats, the easier the adaptation to an amino acid excess, a direct result of higher activity of the catabolic path ways. This may not be true for the kitten, since the hepatic enzymes involved in the catabolism of Met showed activities much lower than those of rats (6,17), and the adaptation was much slower in our experiment with kittens fed an 18% casein diet than for rats fed a 12% casein diet under similar conditions. Young rats fed a 2% Met diet needed 8 d to adapt and gain weight linearly (1.8 g/d versus 3.3 g for control rats), while the same phenomenon took place in 14-21 d in the grow ing kittens (15 g/d compared with 28 g in control kit tens).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Harper, Becker and Stucki (16) suggested that the more protein an animal (rat) eats, the easier the adaptation to an amino acid excess, a direct result of higher activity of the catabolic path ways. This may not be true for the kitten, since the hepatic enzymes involved in the catabolism of Met showed activities much lower than those of rats (6,17), and the adaptation was much slower in our experiment with kittens fed an 18% casein diet than for rats fed a 12% casein diet under similar conditions. Young rats fed a 2% Met diet needed 8 d to adapt and gain weight linearly (1.8 g/d versus 3.3 g for control rats), while the same phenomenon took place in 14-21 d in the grow ing kittens (15 g/d compared with 28 g in control kit tens).…”
Section: Discussioncontrasting
confidence: 60%
“…The subse quent return of cystathionine concentration to normal levels may indicate that there was a delay in the in duction of cystathionase. An increase in activity oc curred faster (8 d) in rats receiving the same level of dietary Met (6). An increase in plasma neutral amino acids, alanine, proline, threonine, serine and asparagine, was found in blood samples taken on d 10 and 42.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…2, methionine is known to be metabolized by two metabolic pathways, i.e., transsulfuration and transamination pathways (11,12). However, the relative contribution of each pathway , especially of the transamination path way, to the methionine metabolism remains unclear (22,23). It is of interest to know which pathway is responsible for the effect of methionine on plasma cholesterol level since the effect can be considered to be associated with the metabolism of methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Bocock et al [17] and Fau et al [18] reported that the activity of methionine adenosyltransferase in the liver of rats with 5/6 nephrectomy increased, and that methionine intake increased methionine adenosyltrans ferase activity. It was suggested that the cause of abnormal metabolim of sulfur-containing amino acids in patients with chronic renal failure was the decreased renal elimi nation, low activities of related enzymes and coenzyme, the low level of vitamin B(,.…”
Section: Discussionmentioning
confidence: 99%